Polymer latexes for preparing elastomeric films with excellent stress retention and flexibility
The development of a polymer latex via free radical emulsion polymerization addresses the poor stress retention and rigidity issues in existing elastomeric films, resulting in improved films for surgical gloves and other applications with reduced manufacturing costs and environmental impact.
Patent Information
- Application Number
- JP2022517718
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-20
- Filing Date
- 2020-09-18
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2040-09-18
AI Technical Summary
Current elastomeric films, particularly those used in surgical gloves, suffer from poor stress retention properties and rigidity, leading to inadequate fit and potential cross-contamination. Additionally, existing materials can cause protein allergy issues and have high processing costs, along with environmental concerns.
A polymer latex is developed through free radical emulsion polymerization of a mixture containing conjugated diene, ethylenically unsaturated nitrile compounds, vinyl aromatic monomers, and ethylenically unsaturated acids, which results in elastomeric films with improved stress retention and flexibility.
The polymer latex produces elastomeric films with enhanced stress retention and flexibility, making them suitable for surgical gloves and other applications, while also reducing processing time and energy consumption in the manufacturing process.
Smart Images

Figure 0007658955000001 
Figure 0007658955000002 
Figure 0007658955000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer latex for the preparation of an elastomeric film exhibiting excellent stress retention and flexibility properties, such an elastomeric film and an article comprising the elastomeric film, a latex composition comprising the polymer latex, and a method for making an article (e.g., a dip-molded article) using the film. [Background technology]
[0002] According to current industry standards, elastomeric films, especially for dip-molding applications, such as examination gloves, are made from compounds containing carboxylated acrylonitrile butadiene latex (XNBR). However, gloves made from these conventional latexes have very poor stress retention properties and are inherently very hard, so such conventional XNBR latexes cannot be used for surgical gloves. Poor stress retention can lead to poor fitting of the glove on the surgeon's forearm, which can result in cross-contamination.
[0003] Therefore, natural latex surgical gloves are often used. However, natural rubber can cause protein allergy problems. Other polymers such as polyisoprene or polychloroprene are also used to make surgical gloves. However, the processing costs of these materials are very high and their production is not environmentally friendly.
[0004] US Patent No. 6,451,893 relates to zinc oxide-free elastomer formulations containing nitrile butadiene latex, sulfur in an amount of 3.0 parts per 100 parts of nitrile rubber, and a sulfur vulcanization accelerator. Gloves made from these formulations have improved stress retention properties. Especially the relatively high amounts of sulfur and sulfur vulcanization accelerator may cause allergy problems.
[0005] WO 00 / 21451 discloses a carboxylated nitrile rubber glove having high stress retention made from a pre-vulcanized carboxylated nitrile latex having 2-6% by weight methacrylic acid.
[0006] US Patent Application Publication No. 2005 / 0154122 describes a two-step polymerization process for producing a dip-formed latex to obtain a soft elastomeric film.
[0007] US Patent Publication No. 2017 / 0099889 relates to gloves exhibiting improved stress retention made from a formulation including a carboxylated nitrile rubber latex crosslinked with aluminum ions, which are considered a potential health hazard.
[0008] According to U.S. Patent No. 7,730,554, gloves exhibiting improved stress retention can be made by a double-dip process using different XNBR latexes in the two dipping steps, which is complicated and increases manufacturing costs.
[0009] It is therefore an object of the present invention to provide a polymer latex that provides an elastomeric film having excellent stress retention properties and excellent flexibility, which may be used in a range of articles, but is particularly suitable for use in surgical glove and condom applications. Summary of the Invention
[0010] The inventors have surprisingly found that elastomeric films made from polymer latexes obtainable by free radical emulsion polymerization of a mixture of ethylenically unsaturated monomers comprising the following components exhibit improved stress retention properties and flexibility: (a) 15 to 99 weight percent conjugated dienes; (b) 0 to 80 weight percent of an ethylenically unsaturated nitrile compound; (c) 0 to 70 weight percent vinyl aromatic monomer; The total amount of the ethylenically unsaturated nitrile compound (b) and the vinyl aromatic monomer (c) is 0.95 to 84.95% by weight; (d) 0.05 to 10 weight percent of an ethylenically unsaturated acid; Here, the ethylenically unsaturated acid includes the following components: (d1) an ethylenically unsaturated acid comprising an acid functional group and a spacer group separating the ethylenically unsaturated group and the acid functional group by at least four atoms; (e) 0 to 65 weight percent of a copolymerizable ethylenically unsaturated compound; wherein monomers (a)-(e) are different from one another and the weight percentages are based on the total monomers in the mixture.
[0011] According to one aspect, the present invention relates to a polymer latex obtainable by free radical emulsion polymerization of a mixture of ethylenically unsaturated monomers comprising: (a) 15 to 99 weight percent conjugated dienes; (b) 0 to 80 weight percent of an ethylenically unsaturated nitrile compound; (c) 0 to 70 weight percent vinyl aromatic monomer; The total amount of the ethylenically unsaturated nitrile compound (b) and the vinyl aromatic monomer (c) is 0.95 to 84.95% by weight; (d) 0.05 to 10 weight percent of an ethylenically unsaturated acid; Here, the ethylenically unsaturated acid includes the following components: (d1) an ethylenically unsaturated acid comprising an acid functional group and a spacer group separating the ethylenically unsaturated group and the acid functional group by at least four atoms; (e) 0 to 65 weight percent of a copolymerizable ethylenically unsaturated compound; wherein monomers (a)-(e) are different from one another and the weight percentages are based on the total monomers.
[0012] According to a further aspect, the present invention relates to the use of the above-mentioned polymer latex for the production of dip-molded articles or for coating or impregnating substrates, preferably textile or ceramic substrates.
[0013] According to a further aspect, the present invention relates to a polymer latex composition comprising the polymer latex of the present invention, wherein monomer (d) comprises an ethylenically unsaturated carboxylic acid, and said composition further comprises an oxirane-functional compound.
[0014] According to a further aspect, the present invention relates to a formulated latex composition suitable for the manufacture of dip-molded articles comprising a polymer latex or a polymer latex composition as defined above, and optionally an adjuvant selected from a sulfur vulcanizing agent, an accelerator for sulfur vulcanization, a crosslinking agent, a polyvalent cation and combinations thereof.
[0015] According to a further aspect, the present invention relates to a method of making a dip-molded article by the following steps: (a) providing a compounded latex composition as defined above; (b) immersing a form having the desired shape of the final article in a coagulant bath containing a solution of metal salts; (c) removing the form from the coagulant bath and optionally drying the form; (d) immersing the former treated in steps (b) and (c) into the compounded latex composition of step (a); (e) solidifying a latex film onto the surface of the mold; (f) removing the latex coated former from the formulated latex composition and optionally immersing the latex coated former in a water bath; (g) optionally drying the latex coated form; (h) heat treating the latex coated mold obtained from step (e) or (f) at a temperature of 40° C. to 180° C., preferably 60° C. to 100° C.; and (i) Removing the latex article from the mold.
[0016] Yet another aspect of the present invention relates to an elastomeric film made from the polymer latex, polymer latex composition or compounded latex composition of the present invention, and an article comprising said elastomeric film, preferably selected from surgical gloves, examination gloves, condoms, catheters, industrial gloves, cloth-support gloves and household gloves. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Detailed Description of the Invention The polymer latex according to one embodiment of the present invention can be obtained by free radical emulsion polymerization of a mixture of ethylenically unsaturated monomers comprising: (a) 15 to 99 weight percent conjugated dienes; (b) 0 to 80 weight percent of an ethylenically unsaturated nitrile compound; (c) 0 to 70 weight percent vinyl aromatic monomer; The total amount of the ethylenically unsaturated nitrile compound (b) and the vinyl aromatic monomer (c) is 0.95 to 84.95% by weight; (d) 0.05 to 10 weight percent of an ethylenically unsaturated acid; Here, the ethylenically unsaturated acid includes the following components: (d1) an ethylenically unsaturated acid comprising an acid functional group and a spacer group separating the ethylenically unsaturated group and the acid functional group by at least four atoms; (e) 0 to 65 weight percent of a copolymerizable ethylenically unsaturated compound; wherein monomers (a)-(e) are different from one another and the weight percentages are based on the total monomers.
[0018] Conjugated diene monomers (a) suitable for the preparation of the polymer latex according to the invention include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 2,4-hexadiene, 1,3-octadiene, 2-methyl-1,3-pentadiene, 2,3-dimethyl-1,3-pentadiene, 3,4-dimethyl-1,3-hexadiene, 2,3-diethyl-1,3-butadiene, 4,5-diethyl-1,3-octadiene, 3-butyl-1,3-octadiene, 3,7-dimethyl-1,3,6-octatriene, 2-methyl-6-methylene-1,7- The conjugated diene monomers include those selected from octadiene, 7-methyl-3-methylene-1,6-octadiene, 1,3,7-octatriene, 2-ethyl-1,3-butadiene, 2-amyl-1,3-butadiene, 3,7-dimethyl-1,3,7-octatriene, 3,7-dimethyl-1,3,6-octatriene, 3,7,11-trimethyl-1,3,6,10-dodecatetraene, 7,11-dimethyl-3-methylene-1,6,10-dodecatriene, 2,6-dimethyl-2,4,6-octatriene, 2-phenyl-1,3-butadiene, 2-methyl-3-isopropyl-1,3-butadiene, 1,3-cyclohexadiene, myrcene, ocimene and farnesene. 1,3-butadiene, isoprene and combinations thereof are preferred conjugated dienes. 1,3-butadiene is the most preferred diene. Typically, the amount of conjugated diene monomer ranges from 15 to 99% by weight, preferably from 20 to 99% by weight, more preferably from 30 to 75% by weight, and most preferably from 40 to 70% by weight, based on the total weight of monomers. Thus, the conjugated diene may be present in an amount of at least 15% by weight, at least 20% by weight, at least 22% by weight, at least 24% by weight, at least 26% by weight, at least 28% by weight, at least 30% by weight, at least 32% by weight, at least 34% by weight, at least 36% by weight, at least 38% by weight, or at least 40% by weight, based on the total weight of ethylenically unsaturated monomers of the polymer latex.
[0019] Thus, conjugated diene monomer can be used in amounts of 95% or less, 90% or less, 85% or less, 80% or less, 78% or less, 76% or less, 74% or less, 72% or less, 70% or less, 68% or less, 66% or less, 64% or less, 62% or less, 60% or less, 58% or less, or 56% or less by weight. One of ordinary skill in the art would understand that any range between any of the explicitly disclosed lower and upper limits is disclosed herein.
[0020] Unsaturated nitrile monomers that can be used to make particles of latex polymer (a) include polymerizable unsaturated aliphatic nitrile monomers containing 2-4 carbon atoms in a linear or branched arrangement, which may be substituted with either acetyl or additional nitrile groups. Such nitrile monomers include acrylonitrile, methacrylonitrile, α-cyanoethyl acrylonitrile, fumaronitrile, and combinations thereof, with acrylonitrile being most preferred. These nitrile monomers may be included in an amount of 0-80% by weight, preferably 1-80% by weight, more preferably 10-70% by weight or 10-60% by weight, even more preferably 15-50% by weight, even more preferably 20-50% by weight, and most preferably 23-43% by weight, based on the total weight of the ethylenically unsaturated monomers for the polymer latex.
[0021] Thus, the unsaturated nitrile may be present in an amount of at least 1 weight percent, 5 weight percent, at least 10 weight percent, at least 12 weight percent, at least 14 weight percent, at least 16 weight percent, at least 18 weight percent, at least 20 weight percent, at least 22 weight percent, at least 24 weight percent, at least 26 weight percent, at least 28 weight percent, at least 30 weight percent, at least 32 weight percent, at least 34 weight percent, at least 36 weight percent, at least 38 weight percent, or at least 40 weight percent based on the total weight of the ethylenically unsaturated monomers for the polymer latex.
[0022] Thus, the unsaturated nitrile monomer can be used in amounts of 80% or less, 75% or less, 73% or less, 70% or less, 68% or less, 66% or less, 64% or less, 62% or less, 60% or less, 58% or less, 56% or less, 54% or less, 52% or less, 50% or less, 48% or less, 46% or less, or 44% or less by weight. One of ordinary skill in the art would understand that any range between any of the explicitly disclosed lower and upper limits is disclosed herein.
[0023] Representative examples of vinyl aromatic monomers (c) include, for example, styrene, α-methylstyrene, vinyltoluene, o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2,4-diisopropylstyrene, 2,4-dimethylstyrene, 4-t-butylstyrene, 5-t-butyl-2-methylstyrene, 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, 4-bromostyrene, 2-methyl-4,6-dichlorostyrene, 2,4-dibromostyrene, vinylnaphthalene, vinyltoluene, vinylxylene, 2-vinylpyridine, 4-vinylpyridine, 1,1-diphenylethylene, substituted 1,1-diphenylethylene, 1,2-diphenylethene and substituted 1,2-diphenylethylene. Mixtures of one or more vinyl aromatic compounds can also be used. Preferred monomers are styrene and α-methylstyrene. The vinyl aromatic compound can be used in the range of 0-70% by weight, preferably 1-70% by weight, more preferably 10-70% by weight, even more preferably 15-60% by weight, even more preferably 15-50% by weight, or 0-25% by weight, more preferably 0-15% by weight, even more preferably 0-10% by weight. Thus, the vinyl aromatic compound can be present in an amount of 60% by weight or less, 50% by weight or less, 40% by weight or less, 35% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, 18% by weight or less, 16% by weight or less, 14% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 6% by weight or less, 4% by weight or less, 2% by weight or less, or 1% by weight or less, based on the total weight of the ethylenically unsaturated monomers for the polymer latex.When present, the vinyl aromatic compound may be present in an amount of at least 1 weight percent, at least 2 weight percent, at least 5 weight percent, at least 10 weight percent, at least 15 weight percent, at least 20 weight percent, at least 25 weight percent, at least 30 weight percent, or at least 35 weight percent, based on the total weight of ethylenically unsaturated monomers for the polymer latex.
[0024] In the monomer mixture for preparing the polymer latex of the present invention, the sum of the ethylenically unsaturated nitrile compound (b) and the vinyl aromatic monomer (c) is 0.95 to 84.95% by weight based on the total monomers in the mixture. Therefore, the vinyl aromatic compound may be completely absent. In such a case, the ethylenically unsaturated nitrile compound is necessarily present, and the latex can be considered as an XNBR latex. Alternatively, the ethylenically unsaturated nitrile compound may be completely absent. In such a case, the latex in which the vinyl aromatic monomer is necessarily present, and in which butadiene is selected as the particularly preferred conjugated diene and styrene is selected as the preferred vinyl aromatic monomer, can be considered as an XSBR latex.
[0025] The monomer mixture for preparing the polymer latex of the present invention comprises 0.05 to 10% by weight of an ethylenically unsaturated acid (d), which comprises an ethylenically unsaturated acid (d1) comprising an acid functional group and a spacer group separating the ethylenically unsaturated group and the acid functional group by at least 4 atoms.
[0026] The acid functional group can be selected from a carboxylic acid group and a phosphorus-containing acid group. Suitable phosphorus-containing acid groups can be selected from a phosphoric acid group and a phosphonic acid group. Preferably, the acid functional group is selected from a carboxylic acid group.
[0027] Monomer (d1) is CHR 2 =CR 1 -AX structure and mixtures thereof: Where: R 1is selected from H and C1-C4 alkyl; R 2 is selected from H and -AX; A is a divalent spacer group separating the ethylenically unsaturated group and the functional group X by at least 4 atoms and is independently represented by each occurrence as -(C(O)-W). n -Y-(O) m -, -(C(O)-W) n -YOC(O)-Y-, and -(CH2) k -O-(C(O)) p -Y-(O) m - selected from n, m, k and p are integers independently selected for each occurrence from 0 and 1; W is -O- or -NR 3 - and R 3 is selected from H and C1-C4 alkyl; Y is, independently at each occurrence, an optionally substituted straight chain, branched chain, cyclic or aromatic C-C 30 is selected from divalent hydrocarbon and heterohydrocarbon groups of X is selected from -C(O)OH, -P(O)(OH)2, with the proviso that when X is -C(O)OH, m is 0; or -AX is -C(O)-O-(YC(O)-O) l —H, where l is an integer from 2 to 10, preferably from 2 to 7.
[0028] Preferably, component (d1) is a carboxy (C2-C 30 ) Alkyl (meth)acrylate, C7-C with terminal ethylenically unsaturated groups 15 is selected from mono(meth)acryloyloxyalkyl esters of fatty acids and dicarboxylic acid esters, more preferably carboxy (C2-C 12 ) alkyl (meth) acrylate and ω-(meth) acryloyloxy (C2-C 12) alkyl succinates, most preferably 2-(meth)acryloyloxyethyl succinate, 2-carboxyethyl acrylate and CH2=CH-C(O)-O-(C2H4-C(O)-O) l -H structure (wherein l is an integer from 2 to 7), and their oligomers, as well as mixtures thereof.
[0029] Suitable monomers (d1) are commercially available from Solvay (Belgium) as Sipomer® β-CEA, Sipomer® PAM100, Sipomer® PAM200, Sipomer® PAM300, Sipomer® PAM4000, Sipomer® PAM5000.
[0030] Typically, the amount of ethylenically unsaturated acid (d) is 0.05 to 10% by weight, in particular 0.1 to 10% by weight or 0.05 to 7% by weight, preferably 0.1 to 9% by weight, more preferably 0.1 to 8% by weight, even more preferably 1 to 7% by weight, most preferably 2 to 7% by weight, based on the total weight of ethylenically unsaturated monomers for the polymer. Thus, the ethylenically unsaturated acid may be present in an amount of at least 0.01% by weight, at least 0.05% by weight, at least 0.1% by weight, at least 0.3% by weight, at least 0.5% by weight, at least 0.7% by weight, at least 0.9% by weight, at least 1% by weight, at least 1.2% by weight, at least 1.4% by weight, at least 1.6% by weight, at least 1.8% by weight, at least 2% by weight, at least 2.5% by weight, or at least 3% by weight. Similarly, the ethylenically unsaturated acid can be present in an amount of 10% or less, 9.5% or less, 9% or less, 8.5% or less, 8% or less, 7.5% or less, 7% or less, 6.5% or less, 6% or less, 5.5% or less, or 5% or less by weight, based on the total weight of ethylenically unsaturated monomers for the polymer latex. One of ordinary skill in the art will understand that any range defined by an explicitly disclosed lower limit and an explicitly disclosed upper limit is herein disclosed.
[0031] The ethylenically unsaturated acid of component (d1) may be present in the mixture of ethylenically unsaturated monomers at 0.05 to 10% by weight, preferably 0.1 to 9% by weight, more preferably 1 to 8% by weight, even more preferably 1 to 6% by weight, even more preferably 2 to 5% by weight, and most preferably 2 to 4% by weight, based on the total monomers in the mixture. According to the invention, the ethylenically unsaturated acid of (d1) may be the only ethylenically unsaturated acid.
[0032] Thus, the ethylenically unsaturated acid (d1) may be present in an amount of at least 0.01%, at least 0.05%, at least 0.1%, at least 0.3%, at least 0.5%, at least 0.7%, at least 0.9%, at least 1%, at least 1.2%, at least 1.4%, at least 1.6%, at least 1.8%, at least 2%, at least 2.5%, or at least 3% by weight. Similarly, the ethylenically unsaturated acid (d1) may be present in an amount of 10% or less, 9.5% or less, 9% or less, 8.5% or less, 8% or less, 7.5% or less, 7% or less, 6.5% or less, 6% or less, 5.5% or less, or 5% or less by weight, based on the total weight of the ethylenically unsaturated monomers for the polymer latex. One of ordinary skill in the art will appreciate that any range defined by an explicitly disclosed lower limit and an explicitly disclosed upper limit is disclosed herein.
[0033] The monomer mixture for the preparation of the polymer latex of the present invention may additionally contain an ethylenically unsaturated acid (d2) different from the ethylenically unsaturated acid (d1). Suitable ethylenically unsaturated carboxylic acids (d2) or salts thereof may be selected from mono- and dicarboxylic acid monomers, their anhydrides and partial esters of polycarboxylic acids. It is preferred to use ethylenically unsaturated aliphatic mono- or dicarboxylic acids or anhydrides containing 3 to 5 carbon atoms. Examples of monocarboxylic acid monomers include acrylic acid, methacrylic acid, crotonic acid, and examples of dicarboxylic acid monomers include fumaric acid, itaconic acid, maleic acid, cis-cyclohexene-1,2-dicarboxylic acid, dimethylmaleic acid, bromomaleic acid, 2,3-dichloromaleic acid, and (2-dodecen-1-yl)succinic acid. Examples of polycarboxylic acid partial esters include monomethyl maleate, monomethyl fumarate, monoethyl maleate, monoethyl fumarate, monopropyl maleate, monopropyl fumarate, monobutyl maleate, monobutyl fumarate, mono(2-ethylhexyl) maleate, mono(2-ethylhexyl) fumarate. Examples of other suitable ethylenically unsaturated acids (d2) include vinyl acetate, vinyl lactate, vinyl sulfonic acid, 2-methyl-2-propene-1-sulfonic acid, styrene sulfonic acid, acrylamidomethylpropane sulfonic acid, and salts thereof. (Meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, and combinations thereof are particularly preferred.
[0034] The ethylenically unsaturated acid (d2) may be present in the monomer mixture for the preparation of the polymer latex of the present invention in an amount that, together with the amount of the ethylenically unsaturated acid (d1), provides the total amount of ethylenically unsaturated monomer as disclosed above.
[0035] According to the present invention, it is particularly preferred that the latex particles exhibit a concentration gradient of functional group (a), with a higher concentration of functional group (a) at the surface of the particle and a lower concentration within the bulk of the particle.
[0036] Furthermore, the mixture of ethylenically unsaturated monomers for the polymer latex according to the invention can contain additional ethylenically unsaturated monomers different from the monomers defined above. These monomers can be selected from the following components: (e1) alkyl esters of ethylenically unsaturated acids; (e2) hydroxyalkyl esters of ethylenically unsaturated acids; (e3) amides of ethylenically unsaturated acids; (e4) vinyl carboxylate; (e5) alkoxyalkyl esters of ethylenically unsaturated acids; (e6) a monomer having at least two ethylenically unsaturated groups; (e7) ethylenically unsaturated silanes; and combinations thereof.
[0037] The vinyl carboxylate monomers that can be used according to the present invention include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl benzoate, vinyl-2-ethylhexanoate, vinyl stearate, and vinyl esters of Versatic acid. The most preferred vinyl ester monomer for use in the present invention is vinyl acetate. Typically, the vinyl ester monomer can be present in an amount of 18% by weight or less, 16% by weight or less, 14% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 6% by weight or less, 4% by weight or less, 2% by weight or less, or 1% by weight or less, based on the total weight of the ethylenically unsaturated monomers for the polymer latex.
[0038] Alkyl esters of ethylenically unsaturated acids that can be used in accordance with the present invention include n-, iso-, or tert-alkyl esters of acrylic or (meth)acrylic acid, in which the alkyl group has 1 to 20 carbon atoms, reaction products of methacrylic acid with glycidyl esters of neo-acids (such as versatic, neodecanoic, or pivalic acid), and hydroxyalkyl and alkoxyalkyl (meth)acrylate monomers.
[0039] Generally, preferred alkyl esters of (meth)acrylic acid are C1-C 10 It can be selected from alkyl (meth)acrylates, preferably C1-C8-alkyl (meth)acrylates. Examples of such acrylate monomers include n-butyl acrylate, secondary butyl acrylate, ethyl acrylate, hexyl acrylate, tert-butyl acrylate, 2-ethyl-hexyl acrylate, isooctyl acrylate, 4-methyl-2-pentyl acrylate, 2-methylbutyl acrylate, methyl methacrylate, butyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, ethyl methacrylate, isopropyl methacrylate, hexyl methacrylate, cyclohexyl methacrylate and cetyl methacrylate. Methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate and combinations thereof are preferred.
[0040] Typically, the alkyl (meth)acrylate monomer can be present in an amount of 18% by weight or less, 16% by weight or less, 14% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 6% by weight or less, 4% by weight or less, 2% by weight or less, or 1% by weight or less, based on the total weight of ethylenically unsaturated monomers for the polymer latex.
[0041] Hydroxyalkyl esters of ethylenically unsaturated acids that can be used to prepare the polymer latex according to the present invention include hydroxyalkyl acrylate and hydroxyalkyl methacrylate monomers based on ethylene oxide, propylene oxide and higher alkylene oxides or mixtures thereof. For example, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate and hydroxybutyl acrylate. Preferably, the hydroxyalkyl (meth)acrylate monomer is 2-hydroxyethyl (meth)acrylate. Typically, the hydroxyalkyl (meth)acrylate monomer can be present in an amount of 18% by weight or less, 16% by weight or less, 14% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 6% by weight or less, 4% by weight or less, 2% by weight or less, or 1% by weight or less based on the total weight of the ethylenically unsaturated monomers for the polymer latex.
[0042] The alkoxyalkyl (meth)acrylate monomers that can be used in the present invention include methoxyethyl methacrylate, ethoxyethyl methacrylate, methoxyethyl methacrylate, ethoxyethyl acrylate, butoxyethyl methacrylate, methoxybutyl acrylate and methoxyethoxyethyl acrylate.Preferred alkoxyalkyl (meth)acrylate monomers are ethoxyethyl acrylate and methoxyethyl acrylate.Typically, the alkoxyethyl alkyl (meth)acrylate monomers can be present in an amount of 18% by weight or less, 16% by weight or less, 14% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 6% by weight or less, 4% by weight or less, 2% by weight or less, or 1% by weight or less based on the total weight of the ethylenically unsaturated monomers for the polymer latex.
[0043] The amides of ethylenically unsaturated acids that can be used to prepare the polymer latex according to the present invention include acrylamide, methacrylamide, and diacetone acrylamide. The preferred amide monomer is (meth)acrylamide. To introduce functional groups capable of self-crosslinking by heat treatment into the polymer particles of the present invention, monomers containing N-methylol amide groups may be employed. Suitable monomers are N-methylol (meth)acrylamide, N-methoxymethyl-(meth)acrylamide, Nn-butoxy-methyl-(meth)acrylamide, N-iso-butoxy-methyl-(meth)acrylamide, N-acetoxymethyl-(meth)acrylamide, N(-2,2-dimethoxy-1-hydroxyethyl)acrylamide. Typically, the amide of an ethylenically unsaturated acid can be present in an amount of 18% by weight or less, 16% by weight or less, 14% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 6% by weight or less, 4% by weight or less, 2% by weight or less, or 1% by weight or less, based on the total weight of ethylenically unsaturated monomers for the polymer latex.
[0044] Suitable monomers (e6) having at least two ethylenically unsaturated groups may be selected from divinylbenzene, diacrylates and di(meth)acrylates. For example, ethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, tripropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate and dipropylene glycol di(meth)acrylate. Monomers having at least two ethylenically unsaturated groups are preferably selected from divinylbenzene, 1,2-ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate and 1,6-hexanediol di(meth)acrylate. Preferred monomers having at least two ethylenically unsaturated groups are preferably selected from divinylbenzene, ethylene glycol dimethacrylate and 1,4-butanediol di(meth)acrylate. The amount of monomers having at least two ethylenically unsaturated groups may be less than 5% by weight, preferably less than 4% by weight, more preferably less than 3% by weight, even more preferably less than 2.5% by weight, even more preferably less than 2% by weight, even more preferably less than 1.5% by weight, based on the total weight of the monomers. The monomer mixture may be free of monomer (e6).
[0045] Suitable silane monomer (e7) can be selected from vinyltrialkoxysilane, allyltrialkoxysilane, and 3-(meth)acryloxypropyltrialkoxysilane. The amount of silane monomer (e7) can be less than 5% by weight, preferably less than 4% by weight, more preferably less than 3% by weight, even more preferably less than 2.5% by weight, even more preferably less than 2% by weight, even more preferably less than 1.5% by weight, based on the total weight of monomers. The monomer mixture can be free of monomer (e7).
[0046] Method for preparing the polymer latex of the present invention The polymer latex according to the invention can be prepared by any emulsion polymerization process known to those skilled in the art, provided that the monomer mixtures defined herein are used. The process described in EP-A-792891 is particularly suitable.
[0047] In the emulsion polymerization for preparing the polymer latex of the present invention, a seed latex may be employed. The seed latex is preferably prepared separately, and the emulsion polymerization is carried out in the presence of the separately prepared seed latex. The seed latex particles are preferably present in an amount of 0.01 to 10, preferably 1 to 5 parts by weight, based on 100 parts by weight of the total ethylenically unsaturated monomers used in the polymer latex, including those for making the seed particles, such as the oxirane-functional latex particles (b). Thus, the lower limit of the amount of seed latex particles can be 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, or 2.5 parts by weight. The upper limit of the above amount can be 10, 9, 8, 7, 6, 5.5, 5, 4.5, 4, 3.8, 3.6, 3.4, 3.3, 3.2, 3.1 or 3 parts by weight. One of ordinary skill in the art will recognize that any range formed by any of the explicitly disclosed lower and upper limits is expressly encompassed herein.
[0048] The above-mentioned process for the preparation of the polymer latex can be carried out in the presence or absence of one or more emulsifiers, in the presence or absence of one or more colloids and in the presence of one or more initiators at temperatures between 0 and 130° C., preferably between 0 and 100° C., particularly preferably between 5 and 70° C. and very particularly preferably between 5 and 60° C., including all values and subvalues therebetween, in particular 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120 and 125° C.
[0049] The initiator that can be used in carrying out the present invention includes water-soluble and / or oil-soluble initiators that are effective for polymerization purposes.Representative initiators are well known in the art, and include, for example, azo compounds (e.g., AIBN, AMBN, and cyanovaleric acid), inorganic peroxy compounds (e.g., hydrogen peroxide, sodium, potassium, and ammonium peroxydisulfates, peroxycarbonates, and peroxyborates), organic peroxy compounds (e.g., alkyl hydroperoxides, dialkyl peroxides, acyl hydroperoxides, and diacyl peroxides), esters (e.g., tertiary butyl perbenzoate), and combinations of inorganic and organic initiators.
[0050] The initiator is used in an amount sufficient to initiate the polymerization reaction at the desired rate. Generally, an amount of initiator of 0.01 to 5 weight percent, preferably 0.1 to 4 weight percent, based on the weight of the total polymer, is sufficient. Most preferably, the amount of initiator is 0.01 to 2 weight percent, based on the total weight of the polymer. The amount of initiator includes all values and subvalues therebetween, particularly including 0.01, 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 4, and 4.5 weight percent, based on the total weight of the polymer.
[0051] The above inorganic and organic peroxy compounds may also be used alone or in combination with one or more suitable reducing agents, as is well known in the art. Examples of such reducing agents that may be mentioned are sulfur dioxide, alkali metal disulfites, alkali metal and ammonium hydrogen sulfites, thiosulfates, dithionite and formaldehyde sulfoxylates, hydroxylamine hydrochloride, hydrazine sulfate, iron(II) sulfate, copper naphthenate, glucose, sulfonic acid compounds such as sodium methanesulfonate, and amine compounds such as dimethylaniline and ascorbic acid. The use of proprietary sodium salts of organic sulfinic acid derivatives, such as Bruggolite® FF6 or Bruggolite® FF6M, is more preferred. The amount of reducing agent is preferably between 0.03 and 10 parts by weight per part by weight of polymerization initiator.
[0052] Suitable surfactants or emulsifiers for stabilizing latex particles include conventional surfactants for polymerization processes. Surfactants can be added to the aqueous phase and / or the monomer phase. In a seeded process, an effective amount of surfactant is an amount selected to support colloidal stabilization of the particles, minimizing interparticle contact and preventing agglomeration. In a non-seeded process, an effective amount of surfactant is an amount selected to affect particle size.
[0053] Representative surfactants include, for example, saturated and ethylenically unsaturated sulfonic acids and their salts, such as unsaturated hydrocarbon sulfonic acids (such as vinyl sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid); aromatic hydrocarbon acids (such as p-styrene sulfonic acid, isopropenyl benzene sulfonic acid, and vinyloxybenzene sulfonic acid) and their salts; sulfoalkyl esters of acrylic and methacrylic acid (such as sulfoethyl methacrylate and sulfopropyl methacrylate) and their salts; and 2-acrylamido-2-methylpropane sulfonic acid and their salts; alkylated diphenyloxide disulfonates, dihexyl esters of sodium dodecylbenzene sulfonate and sodium sulfosuccinate, sodium alkyl esters of sulfonic acids, ethoxylated alkylphenols and ethoxylated alcohols; and fatty alcohol (poly)ether sulfates.
[0054] The type and amount of surfactant is typically governed by the number of particles, their size and their composition. Typically, surfactants are used in an amount of 0-20, preferably 0-10, more preferably 0-5% by weight, based on the total weight of monomers. The amount of surfactant includes all values and subvalues therebetween, in particular 0, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 and 19% by weight, based on the total weight of monomers. According to one embodiment of the present invention, the polymerization is carried out without the use of surfactants.
[0055] Instead of or in addition to the above surfactants, various protective colloids can also be used. Suitable colloids include polyhydroxy compounds such as partially acetylated polyvinyl alcohol, casein, hydroxyethyl starch, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, polysaccharides and decomposed polysaccharides, polyethylene glycols and gum arabic. Preferred protective colloids are carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose. Generally, these protective colloids are used in a content of 0 to 10, preferably 0 to 5, more preferably 0 to 2 parts by weight, based on the total weight of the monomers. The amount of protective colloid includes all values and subvalues therebetween, in particular 1, 2, 3, 4, 5, 6, 7, 8 and 9% by weight, based on the total weight of the monomers.
[0056] Those skilled in the art will understand the type and amount of polar functional monomer, surfactant and protective colloid selected to make the polymer latex according to the present invention suitable for dip molding applications.Thus, it is preferred that the polymer latex composition of the present invention has a certain maximum electrolyte stability determined as a critical coagulation concentration of CaCl2 of less than 30 mmol / l, preferably less than 25 mmol / l, more preferably less than 20 mmol / l, and most preferably less than 10 mmol / l (measured for a total solids content of the composition of 0.1% at pH 10 and 23°C).
[0057] If the electrolyte is too stable, it will be difficult to coagulate the polymer latex in the dip molding process, resulting in either no continuous film of the polymer latex being formed on the former or the thickness of the resulting product being non-uniform.
[0058] It is within the routine of a person skilled in the art to properly adjust the electrolyte stability of the polymer latex. The electrolyte stability depends on certain different factors, such as the amount and selection of monomers (especially those containing polar functional groups) used to prepare the polymer latex, and the selection and amount of stabilizing system (e.g., emulsion polymerization process for preparing the polymer latex). The stabilizing system can contain surfactants and / or protective colloids.
[0059] Depending on the monomers selected and their relative amounts for making the polymer latex of the present invention, one skilled in the art will be able to tailor the stabilization system to achieve electrolyte stability according to the present invention.
[0060] Since there are so many different influences on electrolyte stability, adjustments are best made by trial and error experimentation, but this can be easily done without undue effort using the test methods for electrolyte stability as disclosed above.
[0061] It is often recommended that the emulsion polymerization is further carried out in the presence of buffer substances and chelating agents. Suitable substances are, for example, alkali metal carbonates and hydrogen carbonates, alkali metal phosphates and pyrophosphates (buffer substances) and alkali metal salts of ethylenediaminetetraacetic acid (EDTA) or hydroxyl-2-ethylenediaminetriacetic acid (HEEDTA) as chelating agents. The amount of buffer substances and chelating agents is usually 0.001-1.0% by weight, based on the total amount of monomers.
[0062] In addition, it may be advantageous to use chain transfer agents (regulators) in the emulsion polymerization. Typical agents include, for example, thioesters, 2-mercaptoethanol, 3-mercaptopropionic acid, and C1-C 12The amount of chain transfer agent, if present, is usually 0.05-3.0% by weight, preferably 0.2-2.0% by weight, based on the total weight of the monomers used.
[0063] Additionally, it may be beneficial to introduce partial neutralization into the polymerization process. Those skilled in the art will appreciate that by appropriate selection of this parameter the necessary control may be achieved.
[0064] Polymer Latex Composition The polymer latex composition of the present invention can be prepared by first making a polymer latex as described above, in which monomer (d) comprises an ethylenically unsaturated carboxylic acid, and then mixing the resulting polymer latex with an oxirane functional compound. In the polymer latex composition of the present invention, the carboxylic acid functional polymer latex of the present invention and the oxirane functional compound are present in relative amounts to provide a molar ratio of oxirane groups to carboxylic acid groups of 0.1 to 2, preferably 0.1 to 1.5, more preferably 0.2 to 0.9, and most preferably 0.3 to 0.6.
[0065] The oxirane-functional compound may be selected from the following components: (i) a latex polymer, preferably a butadiene acrylonitrile latex polymer having multiple oxirane functional groups; (ii) a monomeric or oligomeric compound containing at least two oxirane functional groups; and (iii) A monomeric compound, an oligomeric or polymeric compound not prepared by free radical addition polymerization, which has at least one oxirane group and a functional group other than the oxirane group, and wherein said functional groups other than the oxirane group on different molecules of compound (iii) are capable of reacting with each other.
[0066] The latex polymer (i) can be selected from oxirane functional latex polymers as disclosed in WO 2017 / 209596.
[0067] Suitable monomeric or oligomeric compounds (ii) containing at least two oxirane functional groups may be selected from ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, poly(ethylene glycol) diglycidyl ether, poly(propylene glycol) diglycidyl ether, bisphenol-A diglycidyl ether, and combinations thereof.
[0068] Preferably, compound (iii) is selected from oxirane-functional dialkoxysilanes or trialkoxysilanes, more preferably (3-glycidoxypropyl)trialkoxysilane.
[0069] Without wishing to be bound by theory, it is believed that when forming an elastomeric film from a latex composition comprising the carboxylated polymer latex and oxirane functional compound of the present invention, thermally unstable β-hydroxy ester bonds, such as crosslinks, are formed. Upon application of thermal energy, these unstable β-hydroxy ester bonds or crosslinks are broken and then reformed again, such that such elastomeric films exhibit self-healing properties and can be repaired and recycled, providing further advantages to the present invention.
[0070] Formulated latex composition for the production of dip-molded articles The polymer latex of the present invention is particularly suitable for the dip molding process. Therefore, the polymer latex or polymer latex composition of the present invention is formulated to produce a curable polymer latex formulation composition that can be directly used in the dip molding process.
[0071] A compounded latex composition suitable for producing dip molded articles comprises the polymer latex or polymer latex composition of the present invention and an adjuvant selected from a sulfur vulcanizing agent, an accelerator for sulfur vulcanization, a crosslinking agent, a polyvalent cation and combinations thereof. The presence of a polyvalent cation, preferably ZnO, preferably ZnO in an amount of 0.5% to 2.5% by weight based on the solid latex polymer of ZnO is preferred.
[0072] In particular, the compounded latex composition may contain, expressed as weight percentages based on the solid latex polymer, 0-2.8%, preferably 0.5-2.8%, more preferably 1.0-2.0%, and most preferably 1.5-2.0% sulfur and 0.0-2.8%, preferably 1.0-2.0%, more preferably 1.2-1.8% sulfur vulcanizing agent and 0.5%-2.5% ZnO. When a crosslinking agent such as the oxirane functional compounds described above is present, the sulfur vulcanizing agent may be omitted.
[0073] In order to obtain reproducible and good physical film properties, it is desirable to adjust the pH of the compounded polymer latex composition by a pH adjuster to a range of pH 7-13, preferably 10.5-13, more preferably 11-12, for dipping to produce thin disposable gloves. For producing unsupported and / or supported reusable gloves, it is desirable to adjust the pH of the compounded polymer latex composition by a pH adjuster to a range of pH 8-10, preferably 8.5-9.5. The compounded polymer latex composition comprises the polymer latex of the present invention, optionally a pH adjuster, preferably ammonia or an alkali hydroxide, and optionally additives typically used in these compositions and selected from antioxidants, pigments, TiO2, fillers and dispersants.
[0074] Various other additives and ingredients can be added to prepare the latex composition of the present invention. Such additives include, for example, defoamers, wetting agents, thickeners, plasticizers, fillers, pigments, dispersants, optical brighteners, antioxidants, biocides, and metal chelating agents. Known defoamers include silicone oils and acetylene glycols. Commonly known wetting agents include alkylphenol ethoxylates, alkali metal dialkyl sulfosuccinates, acetylene glycols, and alkali metal alkyl sulfates. Typical thickeners include polyacrylates, polyacrylamides, xanthan gum, modified cellulose, or granular thickeners (e.g., silica and clay). Typical plasticizers include mineral oils, liquid polybutenes, liquid polyacrylates, and lanolin. Titanium dioxide (TiO2), calcium carbonate, and clay are typically used fillers.
[0075] How to make dip-molded products In the method of producing a dip-molded latex article according to the present invention, a clean form having the desired shape of the final article is first immersed in a coagulant bath containing a solution of a metal salt. The coagulant is usually used as a solution in water, alcohol or a mixture thereof. As specific examples of coagulants, the metal salts can be metal halides such as calcium chloride, magnesium chloride, barium chloride, zinc chloride and aluminum chloride; metal nitrates such as calcium nitrate, barium nitrate and zinc nitrate; metal sulfates such as calcium sulfate, magnesium sulfate and aluminum sulfate; and acetates such as calcium acetate, barium acetate and zinc acetate. Most preferred are calcium chloride and calcium nitrate. The coagulant solution may also contain additives to improve the wetting behavior of the former.
[0076] The mold is then removed from the bath and optionally dried. The treated mold is then immersed in a compounded latex composition according to the invention, which causes a thin film of latex to solidify on the mold surface. It is known in the art that the thickness of the film thus immersed can be influenced by the concentration of the compounded latex and / or the length of time the salt-coated mold is in contact with the compounded latex. Alternatively, it is also possible to obtain a latex film by performing multiple immersion steps, in particular two immersion steps, in sequence.
[0077] The former is then removed from the latex composition and optionally immersed in a water bath to extract, e.g., polar components from the composition and to wash the coagulated latex film, and then the latex-coated former is optionally dried at a temperature below 80°C.
[0078] Finally, the latex coated mold is heat treated at temperatures between 40 and 180°C to obtain the desired mechanical properties of the final film product. The final latex film is then removed from the mold. The duration of the heat treatment depends on the temperature and is typically between 1 and 60 minutes. The higher the temperature, the shorter the treatment time required.
[0079] The present inventors have surprisingly discovered that when using the polymer latex composition of the present invention, the dip molding process can be carried out more economically. In particular, it has been discovered that the time required between forming the compounded latex composition according to the present invention and carrying out the dip molding step (aging time) can be significantly reduced to 180 minutes or less, as compared to compounds made from standard latexes, which require aging times well in excess of 180 minutes.
[0080] Furthermore, the inventors have found that the temperature of the heat treatment step can be significantly reduced within the range of 40° C. to less than 120° C. without compromising the mechanical properties of the final dip molded article. Conventional latexes require temperatures of 120° C. or higher to achieve the desired mechanical properties. Thus, when using the polymer latexes of the present invention, the dip molding process becomes less time consuming, less energy intensive, and more economical.
[0081] The final heat-treated elastomeric film may have a tensile strength of at least about 7 MPa and an elongation at break of at least about 300%, preferably a tensile strength of at least about 10 MPa and an elongation at break of at least about 350%, more preferably a tensile strength of at least about 15 MPa and an elongation at break of at least about 400%, even more preferably a tensile strength of at least about 20 MPa and an elongation at break of at least about 500%. These mechanical properties were measured according to ASTM D6319. The preferred range of stress retention is 35-80%, preferably 50-70%.
[0082] The dip molding process of the present invention can be used for any latex article that can be manufactured by dip molding processes known in the art. The article can be selected from health care devices formed from or including elastomeric films, surgical gloves, examination gloves, condoms, catheters, or all different kinds of industrial and household gloves. Due to the improved stress retention of the elastomeric films obtained from the polymer latex of the present invention, the polymer latex of the present invention is particularly suitable for the manufacture of surgical gloves and condoms.
[0083] As discussed above, elastomeric films made from the polymer latexes and polymer latex compositions comprising oxirane-functional compounds of the present invention can be repaired and recycled.
[0084] Method for repairing an elastomeric film or an article including said elastomeric film The present invention also relates to a method of repairing an elastomeric film made from the polymer latex composition of the present invention by the following procedure: (a) providing a damaged elastomeric film made from the polymer latex composition of the present invention, or an article including such a damaged elastomeric film, the damaged elastomeric film having at least a surface to be reconnected; (b) rejoining said surfaces of the damaged film; (c) heating or annealing the damaged elastomeric film at a temperature between 40°C and 200°C while maintaining intimate contact with the rejoined surfaces of the damaged elastomeric film;
[0085] The articles formed from the elastomeric film are collected, sorted, and optionally sterilized for handling purposes. Articles that are damaged but not to the point of being unable to be reused are separated, and the damaged surfaces are optionally further cleaned. This cleaning can be by washing with hydrogen peroxide or other sterilizing fluids, or by passing under a carbon dioxide air stream or UV light to ensure the absence of pathogens. At the location of the damage, the surfaces of the damaged film that were separated from each other are brought together so that they are in contact with each other, for example, if there is a hole, the edges of the hole are brought together, and the surfaces are heated to soften the elastomeric film and the surfaces seal together to repair the damage, after which the surfaces are cooled to expose the repaired or self-healed surface. The heating can be done while applying pressure to the contact area of the damaged surfaces.
[0086] Method for recycling elastomeric films or articles containing elastomeric films The present invention also relates to a method for recycling an elastomeric film made from the polymer latex composition of the present invention or an article comprising such an elastomeric film by cutting, shredding or grinding the elastomeric film or article according to the present invention to form particles of elastomer, optionally blending the resulting particles with particles of virgin elastomer, and exposing the particles to a pressure of 1-20 MPa and a temperature of 40° C.-200° C. to form the recycled film or article.
[0087] The elastomeric materials, such as gloves, are collected and, if necessary, sorted so that nitrile-containing materials are collected together, while other materials are discarded or sent to an alternative recycling or reprocessing facility. The collected materials are then washed and decontaminated as necessary, similar to what is done for the repair / self-healing process. The materials are then ground to a particle size of 2 mm or less in average diameter, preferably 1 mm or less in average diameter, and ideally with an average particle size diameter in the range of 0.15-0.75, more preferably 0.2-0.3. The grinding or milling process can be carried out below room temperature, or indeed under cryogenic conditions, to allow for easy processing and to maintain the material as particles before further processing. The cryogenic conditions avoid recombination of the particles until required. The materials can be stored at room temperature or under conditions such as to avoid recombination of the particles until required. The materials may be further ground before being fed to a blender, where the materials are blended with other materials, such as particles of virgin elastomeric material, and conventional processing aids and additives. In the absence of a blending step, the material is fed directly into a heat treatment system where the particles / crumbs are hot pressed, two roll milled, calendared or extruded under pressure and heat, i.e. at temperatures above 40°C, to give the material flowability by breaking bonds within the material (e.g., β-hydroxy ester bonds within the material), at which stage the material can also be formed into the required final shape. The material is then cooled, as required, in a mold or as part of the extrusion process to produce the final product formed from the recycled material.
[0088] The invention will now be further described with reference to the following examples. EXAMPLES
[0089] Measurement of physical parameters The dispersions were characterized by measuring the total solids content (TSC), pH value, viscosity (Brookfield LVT) and z-average particle size. Additionally, the final films were tested for tensile properties.
[0090] Determination of Total Solids Content (TSC): The determination of total solids was based on gravimetric method. 1-2 g of the dispersion was placed in a pre-weighed aluminum pan on an analytical balance. The pan was stored at 120°C for 1 hour in an air circulating oven until a constant mass was reached. After cooling to room temperature, the final weight was remeasured. The solids content was calculated as follows:
number
[0091] Measurement of pH value: The pH value was determined according to DIN ISO 976. After applying a two-point calibration with a buffer solution, the electrode of a Schott CG840 pH meter was immersed in the dispersion at 23° C. and the constant value on the display was recorded as the pH value.
[0092] Viscosity measurement: Latex viscosity was measured at 23°C using a Brookfield LVT viscometer. Approximately 220 ml of liquid (without air bubbles) was filled into a 250 ml beaker and the viscometer spindle was immersed up to the mark on the spindle. The viscometer was then switched on and recorded until the value was constant after about 1 minute. The viscosity range determines the choice of spindle and rotation speed and the factor of the recorded value to calculate the viscosity. Information on the spindle and revolutions per minute used is given in brackets in the examples.
[0093] Particle size (PS) measurement: The z-average particle size was measured using a Malvern Zetasizer Nano S (ZEN1600) that employs dynamic light scattering. The latex sample was diluted with deionized water to the turbidity level specified in the manual and transferred to a test cuvette. The cuvette was gently mixed to homogenize the sample and the cuvette was placed in the measurement instrument. The value was recorded as the z-average particle size generated by the software.
[0094] Preparation of immersion films: The nitrile latex with the compounded ingredients at the desired pH value was stirred at room temperature for 24 hours unless otherwise noted in the individual examples below, and then impregnated with a coagulant as follows.
[0095] Ceramic spades were washed with soap and then rinsed thoroughly with deionized water, after which they were dried in an air-circulating oven set at 65-70°C (spade temperature, 55-60°C) until dry. A coagulant solution was prepared by dissolving calcium nitrate (18 wt%) and calcium carbonate (2 wt%) in deionized water. The dried spade was then dipped into the salt solution, removed, and then dried in an air circulating oven set at 70-75°C (spade temperature, 60-65°C) until dry. The salt-coated spade was then dipped into the desired formulated latex (having 18% total solids by weight, and aged at room temperature for 24 hours after formulation) for a dwell time of 5 seconds, after which it was removed and the latex-coated spade was placed in an air circulating oven set at 100°C for 1 minute to gel the film. The thus gelled film was then washed for 1 minute in a tank of deionised water set at 50-60°C and then cured for 20 minutes in an air circulating oven set at 120°C, after which the thus cured / vulcanised film was cooled and removed from the spade and then aged for 22 hours in an air circulating oven set at 100°C. Finally, the cured film was peeled off the spade by hand, with a typical dry film thickness of 0.056-0.066 mm.
[0096] Films prepared from the latex were tested for their tensile strength properties and stress retention behavior.
[0097] Tensile strength property measurements: The tensile properties of the vulcanized films / gloves were tested according to ASTM6319 and dumbbell specimens were cut from gloves prepared from each latex compound using an ASTM D412 C-type cutter (narrow width = 6mm, narrow length = 33mm, total length = 115mm, dumbbell thickness is given in the results table) and tested on a Hounsfield HK10KS tensile meter fitted with an H500LC extensometer at an extension rate of 500mm / min.
[0098] Measurement of stress retention properties: Tensile stress was measured on the dumbbell samples by a tensometer (same as above). Stress retention (%) is defined as the ratio (%) of I6 / I0x100, where I0 is the initial stress measured immediately after the elongation reaches 100%, and I6 is the stress measured after 6 minutes of holding the specimen at 100% elongation.
[0099] In the examples, the following abbreviations are used: MAA = methacrylic acid Bd = butadiene ACN = acrylonitrile tDDM = tert-dodecyl mercaptan Na4EDTA = tetrasodium salt of ethylenediaminetetraacetic acid TSC = Total Solids PS = particle size ZnO = zinc oxide ZDEC = zinc diethyldithiocarbamate S = Sulfur
[0100] Below, all parts and percentages are by weight unless otherwise stated.
[0101] Example 1: Preparation of dip-coated films (control) A nitrogen purged autoclave was charged with 2 parts by weight (based on polymer solids) of seed latex (average particle size 36 nm) and 807 parts by weight of water (based on 100 parts by weight of monomers including seed latex) and heated to 30°C. Then 0.01 parts by weight of Na4EDTA and 0.005 parts by weight of Bruggolite FF6 dissolved in 2 parts by weight of water were added, followed by 0.08 parts by weight of sodium persulfate dissolved in 2 parts by weight of water. Next, monomers (35 parts by weight of acrylonitrile, 57 parts by weight of butadiene, 6 parts by weight of methacrylic acid) were added over 6 hours along with 0.6 parts by weight of tDDM. Over 10 hours, 2.2 parts by weight of sodium dodecylbenzenesulfonate, 0.2 parts by weight of tetrasodium pyrophosphate and 22 parts by weight of water were added. A coactivator feed of 0.13 parts by weight of Bruggolite FF6 in 8 parts by weight of water was added over 9 hours. The temperature was maintained at 30°C until 95% conversion and 45% total solids. The polymerization was briefly stopped by the addition of 0.08 parts by weight of a 5% aqueous solution of diethylhydroxylamine. The pH was adjusted to 7.5 with potassium hydroxide (5% aqueous solution) and residual monomer was removed by vacuum distillation at 60°C. 0.5 parts by weight of Wingstay L type antioxidant (60% dispersion in water) was added to the raw latex and the pH was adjusted to 8.2 by the addition of a 5% aqueous solution of potassium hydroxide.
[0102] For Example 1, the following characterization results were obtained: TSC=45.0wt% pH=8.2 Tg = -15℃ Viscosity=30.5mPas(1 / 60) Particle size, P z =120nm
[0103] The salt coated and dried spades were immersed in a diluted formulated latex solution of 18% TSC with 0.8 phr S, 0.7 phr ZDEC, 1 phr ZnO and titanium dioxide at pH 10 for a 5 second dwell, gelled at 100°C for 1 minute, washed in deionized water for 1 minute (in a bath set at 50-60°C), and then dried and cured / vulcanized in an air circulating oven set at 120°C for 20 minutes to ensure complete drying and crosslinking. The tensile and stress retention properties are shown in Table 1 below.
[0104] Example 1a Example 1 was repeated except that the immersion was carried out as follows. The salt coated and dried spades were immersed in a diluted formulated latex solution of 18% TSC with 1.5 phr S, 1.2 phr ZDEC, 0.9 phr ZnO and titanium dioxide at pH 10 for a 5 second dwell, gelled at 100°C for 3 minutes, washed in deionized water for 1 minute (in a bath set at 50-60°C), and then dried and cured / vulcanized in an air circulating oven set at 120°C for 20 minutes to ensure complete drying and crosslinking. The tensile and stress retention properties are shown in Table 1 below.
[0105] Example 2: (10% substitution of MAA) A composition was prepared similarly to Example 1, except that 5.4 parts of methacrylic acid and 0.6 parts of Sipomer® β-CEA (a mixture of 2-carboxyethyl acrylate oligomers commercially available from Solvay, Belgium) were used.
[0106] Example 3: (20% substitution of MAA) A composition was prepared similar to Example 1, except that 4.8 parts methacrylic acid and 1.2 parts Sipomer® β-CEA were used.
[0107] Example 4: (30% substitution of MAA) A composition was prepared similar to Example 1, except that 4.2 parts methacrylic acid and 1.8 parts Sipomer® β-CEA were used.
[0108] Example 5: (40% substitution of MAA) A composition was prepared similar to Example 1, except that 3.6 parts methacrylic acid and 2.4 parts Sipomer® β-CEA were used.
[0109] Example 6: (100% use of 2-carboxyethyl acrylate oligomer) A composition was prepared similar to Example 1, except that no methacrylic acid was used and 6 parts of Sipomer® β-CEA was used.
[0110] Example 6a (100% use of 2-carboxyethyl acrylate oligomer) A composition was prepared similar to Example 1a, except that no methacrylic acid was used and 6 parts of Sipomer® β-CEA was used.
[0111] Example 7: (100% use of 2-carboxyethyl acrylate oligomer, formulation V1) A composition was prepared similar to Example 1, except that no methacrylic acid was used, and 6 parts of Sipomer® β-CEA was used, and the compounded latex formulation also contained 0.9 phr ZnO, 1.5 phr S, and 1.2 phr ZDEC.
[0112] Example 8: (Formulation V1 with 100% 2-Carboxyethyl Acrylate Oligomer, longer cure time) A composition was prepared similar to Example 1, except that no methacrylic acid was used, and 6 parts of Sipomer® β-CEA were used. The compounded latex formulation also contained 0.9 phr ZnO, 1.5 phr S, and 1.2 phr ZDEC. Curing / vulcanization was carried out for 35 minutes instead of 20 minutes.
[0113] Example 9: (100% use of 2-acryloyloxyethyl succinate) A composition was prepared similar to Example 1a, except that no methacrylic acid was used and 6 parts of 2-acryloyloxyethyl succinate was used.
[0114] [Table 1]
[0115] Example 10: (Control, thick gloves) This was an exact repeat of Example 1.
[0116] Example 11: (100% 2-carboxyethyl acrylate oligomer, thick glove, 35 minute cure time, formulation V1) A composition was prepared similar to Example 1, except that no methacrylic acid was used, and 6 parts of Sipomer® β-CEA were used. Also, the compounded latex was not diluted, and the compounded formulation contained 0.9 phr ZnO, 1.5 phr S, and 1.2 phr ZDEC. Curing / vulcanization was carried out for 35 minutes instead of 20 minutes.
[0117] Example 12: (100% 2-carboxyethyl acrylate oligomer, thick gloves, 40 minute cure time, formulation V1) A composition was prepared similar to Example 1, except that no methacrylic acid was used, 6 parts of Sipomer® β-CEA was used, the compounded latex was not diluted, and the compounded formulation contained 0.9 phr ZnO, 1.5 phr S, and 1.2 phr ZDEC. The cure / vulcanization was carried out for 40 minutes instead of 20 minutes.
[0118] Example 13: (100% 2-carboxyethyl acrylate oligomer, thick gloves, 150 minute cure time, formulation V1) A composition was prepared similar to Example 1, except that no methacrylic acid was used, and 6 parts of Sipomer® β-CEA were used. Also, the compounded latex was not diluted, and the compounded formulation contained 0.9 phr ZnO, 1.5 phr S, and 1.2 phr ZDEC. Curing / vulcanization was carried out for 50 minutes instead of 20 minutes.
[0119] The tensile properties and stress retention properties of Examples 8 to 12 are shown in Table 2 below.
[0120] [Table 2]
[0121] Example 14: (Control with 48 hour maturation time) The composition was prepared as in Example 1, except that the compounded latex was stirred at room temperature for 48 hours instead of 24 hours, and then soaking was performed.
[0122] Example 15: (100% 2-Carboxyethyl Acrylate Oligomer, 35 minute cure time, Formulation V2) A composition was prepared similar to Example 1, except that no methacrylic acid was used and 6 parts of Sipomer® β-CEA was used. The compounded latex formulation also contained 0.3 phr ZnO, 2 phr S, and 0.5 phr ZDEC. The compounded latex was stirred at room temperature for 48 hours instead of 24 hours before immersion. Curing / vulcanization was carried out for 35 minutes instead of 20 minutes.
[0123] Example 16: (100% 2-Carboxyethyl Acrylate Oligomer, 35 minute cure time, Formulation V3) A composition was prepared similar to Example 1, except that no methacrylic acid was used and 6 parts of Sipomer® β-CEA was used. The compounded latex formulation also contained 0.3 phr ZnO, 2 phr S, and 1 phr ZDEC. The compounded latex was stirred at room temperature for 48 hours instead of 24 hours before immersion. Curing / vulcanization was carried out for 35 minutes instead of 20 minutes.
[0124] The tensile properties and stress retention properties of Examples 13 to 15 are shown in Table 3 below.
[0125] [Table 3]
Claims
1. A polymer latex composition comprising a polymer latex for the preparation of elastomeric films obtainable by free radical emulsion polymerization of a mixture of ethylenically unsaturated monomers comprising: (a) 15 to 99 weight percent of a conjugated diene; (b) 0 to 80% by weight of an ethylenically unsaturated nitrile compound; (c) 0 to 70 weight percent of a vinyl aromatic monomer; The sum of the ethylenically unsaturated nitrile compound (b) and the vinyl aromatic monomer (c) is 0.95 to 84.95% by weight; (d) 0.05 to 10 weight percent of an ethylenically unsaturated acid; Here, the ethylenically unsaturated acid includes the following components: (d1) an ethylenically unsaturated acid comprising an acid functional group and a spacer group separating the ethylenically unsaturated group and the acid functional group by at least four atoms; (e) 0 to 65% by weight of a copolymerizable ethylenically unsaturated compound; wherein monomers (a)-(e) are different from one another and the weight percentages are based on the total monomers in the mixture; Monomer (d) comprises an ethylenically unsaturated carboxylic acid and the composition further comprises an oxirane-functional compound.
2. 10. The polymer latex composition of claim 1, wherein the acid functional groups are selected from carboxylic acid groups and phosphorus-containing acid groups.
3. The component (d1) is CHR 2 =CR 1 The polymer latex composition according to claim 1 or 2, which is selected from compounds having the structure of -A-X and mixtures thereof: Where: R 1 is H and C 1 -C 4 alkyl, R 2 is selected from H and -AX; A is a divalent spacer group separating the ethylenically unsaturated group and the functional group X by at least 4 atoms and is independently -(C(O)-W) n -Y-(O) m -, -(C(O)-W) n -Y-O-C(O)-Y-, and -(CH 2 ) k -O-(C(O)) p -Y-(O) m - selected from n, m, k and p are integers independently selected at each occurrence from 0 and 1; W is -O- or -NR 3 - and R 3 is H and C 1 -C 4 alkyl, Y is, independently at each occurrence, an optionally substituted straight chain, branched chain, cyclic or aromatic C 2 -C 30 is selected from divalent hydrocarbon and heterohydrocarbon groups of the formula: X is -C(O)OH, -P(O)(OH) 2 with the proviso that when X is -C(O)OH, then m is 0; or -AX is -C(O)-O-(Y-C(O)-O) l —H, where l is 2-10.
4. The polymer latex composition of any one of claims 1 to 3, wherein the ethylenically unsaturated acid of component (d1) is present at 0.05 to 10% by weight, based on the total monomers in the mixture.
5. The polymer latex composition of any one of claims 1 to 4, wherein the ethylenically unsaturated acid of component (d1) is the only ethylenically unsaturated acid.
6. The polymer latex composition according to any one of claims 1 to 4, wherein the ethylenically unsaturated acid further comprises an ethylenically unsaturated acid (d2) selected from the following: - ethylenically unsaturated carboxylic acids and their salts, - ethylenically unsaturated polycarboxylic acid anhydrides, Polycarboxylic acid partial ester monomers and their salts.
7. (a) the conjugated diene is selected from butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, myrcene, ocimene, farnacene, and combinations thereof; (b) the ethylenically unsaturated nitrile compound is selected from (meth)acrylonitrile, α-cyanoethyl acrylonitrile, fumaronitrile, α-chloronitrile, and combinations thereof; (c) the vinyl aromatic monomer is selected from styrene, alpha-methylstyrene, vinyltoluene, and combinations thereof; (e) the copolymerizable ethylenically unsaturated compound is selected from: (e1) alkyl esters of ethylenically unsaturated acids; (e2) hydroxyalkyl esters of ethylenically unsaturated acids; (e3) amides of ethylenically unsaturated acids; (e4) vinyl carboxylate; (e5) alkoxyalkyl esters of ethylenically unsaturated acids; (e6) a monomer having at least two ethylenically unsaturated groups; (e7) ethylenically unsaturated silanes and combinations thereof; The polymer latex composition according to any one of claims 1 to 6.
8. The polymer latex composition of any one of claims 1 to 7, wherein the mixture of ethylenically unsaturated monomers for the polymer latex comprises: (a) 20 to 98 weight percent of a conjugated diene; (b) 1 to 60% by weight of an ethylenically unsaturated nitrile compound; (c) 0 to 40 weight percent of a vinyl aromatic monomer; (d) 1 to 8 weight percent of an ethylenically unsaturated acid; (e1) 0 to 25% by weight of C 1 -C 8 Alkyl (meth)acrylate; (e3) 0 to 10% by weight of an amide of an ethylenically unsaturated acid; (e4) 0 to 10% by weight of a vinyl ester; (e7) 0 to 10% by weight of an ethylenically unsaturated silane; The weight percentages are based on the total monomers in the mixture.
9. Use of the polymer latex composition according to any one of claims 1 to 8 for the production of dip-molded articles or for coating or impregnating substrates.
10. 2. The polymer latex composition of claim 1, wherein the oxirane functional compound is selected from the following: (i) a latex polymer; (ii) a monomeric or oligomeric compound containing at least two oxirane functional groups; and (iii) A monomeric compound, an oligomeric or polymeric compound not prepared by free radical addition polymerization, which has at least one oxirane group and a functional group other than the oxirane group, and said functional groups other than the oxirane group on different molecules of compound (iii) are capable of reacting with each other.
11. The polymer latex composition of claim 1, wherein the carboxylic acid functional polymer latex and the oxirane functional compound in the polymer latex composition are present in relative amounts providing a molar ratio of oxirane groups to carboxylic acid groups of 0.1 to 2.
12. A compounded latex composition suitable for producing a dip-molded article, comprising the polymer latex composition according to any one of claims 1 to 8, 10 and 11, and an adjuvant selected from a sulfur vulcanizing agent, an accelerator for sulfur vulcanization, a crosslinking agent, a polyvalent cation and combinations thereof.
13. 13. The compounded latex composition of claim 12 comprising 0.0 to 2.8 weight percent of a sulfur vulcanizing agent and 0.5 to 2.5 weight percent of ZnO, expressed as weight percentages based on the solid latex polymer.
14. A method for producing a dip-molded product by the following steps: (a) providing a compounded latex composition according to claim 12 or 13; (b) immersing a form having the desired shape of the final article in a coagulant bath containing a solution of metal salts; (c) removing the form from the coagulant bath and optionally drying the form; (d) immersing the former treated in steps (b) and (c) into the compounded latex composition of step (a); (e) coagulating a latex film onto the surface of the mold; (f) removing the latex coated former from the compounded latex composition and optionally immersing the latex coated former in a water bath; (g) optionally drying the latex coated former; (h) heat treating the latex coated former obtained from step (e) or (f) at a temperature of 40° C. to 180° C.; and (i) Removing the latex article from the mold.
15. 15. The method of claim 14, wherein after step (a) and before step (d), the compounded latex composition is aged for at least 3 hours.
16. An elastomeric film made from the latex composition of any one of claims 1 to 8, 10 and 11, or the compounded latex composition of claim 12 or 13.
17. 17. An article comprising the elastomeric film of claim 16, selected from a surgical glove, an examination glove, a condom, a catheter, an industrial glove, a cloth-supported glove, and a household glove.
18. A method for repairing the elastomeric film of claim 16 or the article of claim 17 by the steps of: (a) providing the elastomeric film of claim 16 having a damage, or the article of claim 17 comprising the elastomeric film having a damage, wherein the damaged elastomeric film has at least a surface to be reconnected; (b) rejoining said surface of the damaged film; (c) heating or annealing the damaged elastomeric film at a temperature between 40° C. and 200° C. while maintaining intimate contact of the rejoined surfaces of the damaged elastomeric film.
19. A method for recycling the elastomeric film of claim 16 or the article of claim 17 containing an elastomeric film, comprising cutting, shredding or grinding the elastomeric film or article to form particles of elastomer, optionally blending the resulting particles with particles of virgin elastomer, and exposing the particles to a pressure of 1 to 20 MPa and a temperature of 40°C to 200°C to form a recycled film or article.
Citation Information
Patent Citations
Copolymer latexs
JP1977134695A
Carbonic acid-modified nitrile-based copolymer latex composition, latex composition comprising same for dip molding, and molded product therefrom
WO2020130330A1